1987
DOI: 10.1248/cpb.35.3375
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of and drug release from W/O/W type double emulsions containing anticancer agents using an oily lymphographic agent as an oil phase.

Abstract: W/O/W type double emulsions stable for a long time were prepared by two-step emulsification procedures using an oily lymphographic agent, Lipiodol Ultra-Fluid, and a derivative of hydrogenated castor oil (HCO-10) as an oil phase. The yield of W/O/W type double emulsions was about 90%. Although the yield was not lowered by vigorous dispersion with a homogenizer, the size of oil droplets was decreased and the release rate of cytarabine was enhanced. Neither the concentration of cytarabine in, nor the volume of, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

1991
1991
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…Therefore, due to their structure and properties, multiple emulsions are of high interest for several fields of application such as carriers for dermal drug delivery of active pharmaceutical ingredients in pharmaceuticals [1][2][3], cosmetics [4] and e.g. for the encapsulation of flavours in food [5].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, due to their structure and properties, multiple emulsions are of high interest for several fields of application such as carriers for dermal drug delivery of active pharmaceutical ingredients in pharmaceuticals [1][2][3], cosmetics [4] and e.g. for the encapsulation of flavours in food [5].…”
Section: Introductionmentioning
confidence: 99%
“…The surface tension, viscosity, and electrostatic interactions being dependent on the ionic strength of the medium (Eqs. (5), (7), and (10)) affect the value of critical shear rate and parameter E (Eq. (9)) and hence the size and number of droplets.…”
Section: Resultsmentioning
confidence: 99%
“…Emulsions are considered to be very important fluids due to their specific characteristics and applications in medicine and the petroleum, chemical, and food industries [1][2][3][4][5][6][7][8]. The work reported up to now is mostly on complicated systems consisting of water, oils, electrolytes, surfactants, and several other such materials [9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…However, pharmaceuticals and nutraceuticals usually have a more complex molecular structure with both polar and non-polar moieties. The articles describing encapsulation of pharmaceuticals and nutraceuticals usually reports significantly lower initial and long term encapsulation efficiency compared to small model compounds with non-amphiphilic nature (Fukushima, Nishida, & Nakano, 1987;Hino, Shimabayashi, Tanaka, Nakano, & Okochi, 2001;O'Regan & Mulvihill, 2010;Paul, Kumar, Yedurkar, & Sawant, 2013). Preliminary studies in our lab have also shown that highly polar/ionic model compounds without hydrophobic domains/moieties are easily entrapped, while drugs with small non-polar moieties are released at a much higher rate, including ionic substances with lipophilic moieties.…”
Section: Introductionmentioning
confidence: 99%